Avoiding apple bud damage from autumnapplied urea for black spot (Venturia inaequalis) control - Wood, P.N.; Beresford, R.M (New Zealand Plant Protection, 2000)
Three field trials in Hawkes Bay and Pukekohe which involved the apple cvs Braeburn Royal Gala Fuji and Granny Smith showed that urea applied to trees in autumn for black spot (Venturia inaequalis) control at concentrations >5 was associated with death of apple buds the following spring Urea containing 09 biuret caused significantly more bud death than urea with 035 biuret but the toxicity of biuret appeared to be unimportant compared to the toxicity of the urea itself when urea was applied at concentrations >5 There was no cumulative bud damage between seasons when urea was applied at 5 in four successive autumns Multiple applications of urea in a single autumn caused bud death and it appeared that the total amount of urea applied in one year should not exceed 100 kg/ha (equivalent to one application of 5 urea)